Evaluating Confounding Control in Estimations of Influenza Antiviral Effectiveness in Electronic Health Plan Data. Issue 5 (2nd February 2022) - Htoo, Phyo T; Measer, Gregory; Orr, Robert; Bohn, Justin; Sorbello, Alfred; Francis, Henry; Dutcher, Sarah K; Cosgrove, Austin; Carruth, Amanda; Toh, Sengwee; Cocoros, Noelle M
Abstract: Observational studies of oseltamivir use and influenza complications could suffer from residual confounding. Using negative control risk periods and a negative control outcome, we examined confounding control in a health-insurance-claims–based study of oseltamivir and influenza complications (pneumonia, all-cause hospitalization, and dispensing of an antibiotic). Within the Food and Drug Administration's Sentinel System, we identified individuals aged ≥18 years who initiated oseltamivir use on the influenza diagnosis date versus those who did not, during 3 influenza seasons (2014–2017). We evaluated primary outcomes within the following 1–30 days (the primary risk period) and 61–90 days (the negative control period) and nonvertebral fractures (the negative control outcome) within days 1–30. We estimated propensity-score–matched risk ratios (RRs) per season. During the 2014–2015 influenza season, oseltamivir use was associated with a reduction in the risk of pneumonia (RR = 0.72, 95% confidence interval (CI): 0.70, 0.75) and all-cause hospitalization (RR = 0.54, 95% CI: 0.53, 0.55) in days 1–30. During days 61–90, estimates were near-null for pneumonia (RR = 1.04, 95% CI: 0.95, 1.15) and hospitalization (RR = 0.94, 95% CI: 0.91, 0.98) but slightly increased for antibiotic dispensing (RR = 1.14, 95% CI: 1.08, 1.21). The RR for fractures was near-null (RR = 1.09, 95% CI: 0.99, 1.20). Estimates for the 2016–2017 influenza season were comparable, while the 2015–2016 season had conflicting results. Our study suggests minimal residual confounding for specific outcomes, but results differed by season.